Research on Battery Energy Storage STATCOM Suppressing HVDC Commutation Failure - Xing, Chao; Chen, Junhao; Xu, Zhi; Xi, Xinze; He, Xin; Chen, Shilong (Frontiers in Energy Research, 2022)
Due to the poor performance of traditional STATCOM in DC engineering, a compensation method using battery energy storage STATCOM (STATCOM/BESS) to suppress commutation failure of weak receiving-end High Voltage Direct Current transmission system is proposed, and its effect is better than traditional STATCOM.Firstly, the mechanism and influencing factors of commutation failure are analyzed; the extinction angle of converter valve is taken as the decision index of commutation failure; the relationship between various electrical parameters and extinction angle is studied under the condition of single-phase grounding fault on inverter side. Secondly, according to the differences between the positive and negative sequence reactive current output by STATCOM/BESS when a fault occurs in single-phase grounding, a compensation method is proposed to suppress commutation failure by STATCOM/BESS, which increases the proportion of positive sequence reactive current output by STATCOM/BESS under the condition of constant output so as to reduce the probability of commutation failure. At last, STATCOM/BESS is added into standard model of LCC-HVDC for simulation experiment, and compare with conventional running characteristics of STATCOM in order to verify the effect of STATCOM/BESS in suppressing commutation failure.